Kawasaki Disease: Laboratory Findings and an Immunopathogenesis on the Premise of a "Protein Homeostasis System" - Lee, Kyung-Yil (Yonsei University College of Medicine, 2012)
Kawasaki disease (KD) is a self-limited systemic inflammatory illness, and coronary artery lesions (CALs) are a major complication determining the prognosis of the disease. Epidemiologic studies in Asian children suggest that the etiologic agent(s) of KD may be associated with environmental changes. Laboratory findings are useful for the diagnosis of incomplete KD, and they can guide the next-step in treatment of initial intravenous immunoglobulin non-responders. CALs seem to develop in the early stages of the disease before a peak in inflammation. Therefore early treatment, before the peak in inflammation, is mandatory to reduce the risk of CAL progression and severity of CALs. The immunopathogenesis of KD is more likely that of acute rheumatic fever than scarlet fever. A hypothetical pathogenesis of KD is proposed under the premise of a "protein homeostasis system"; where innate and adaptive immune cells control pathogenic proteins that are toxic to host cells at a molecular level. After an infection of unknown KD pathogen(s), the pathogenic proteins produced from an unknown focus, spread and bind to endothelial cells of coronary arteries as main target cells. To control the action of pathogenic proteins and/or substances from the injured cells, immune cells are activated. Initially, non-specific T cells and non-specific antibodies are involved in this reaction, while hyperactivated immune cells produce various cytokines, leading to a cytokine imbalance associated with further endothelial cell injury. After the emergence of specific T cells and specific antibodies against the pathogenic proteins, tissue injury ceases and a repair reaction begins with the immune cells.